Use of Imaging in Trauma Decision-Making. Issue Volume 157:Issue (2011)Supplement 3 (1st September 2011) - Gay, DAT; Miles, R
Abstract : Damage Control Radiology describes the process where imaging aids the decision making process in a trauma setting and is an important part of Damage Control Surgery and Resuscitation. This article outlines how radiology fits in to the primary and secondary surveys and discusses the role of imaging modalities such as ultrasound and CT. The importance of deployed radiology to aid rapid diagnosis and decision making is described.